SIFAT DAN KARAKTERISTIK CAMPURAN BETON MENGGUNAKAN BATU PECAH DAN BATU GULI DARI SUNGAI BINJAI - Simanjuntak, Johan Oberlyn; Sidabutar, Ros Anita; Pasaribu, Humisar; Saragi, Yetty Riris R; Sitorus, Sriyanti (Jurnal Visi Eksakta, 2021)
Concrete is a construction material consisting of a mixture of cement, aggregate, water and with or without admixture if needed. Coarse aggregate and fine aggregate serve as the main filler of concrete as well as reinforcement, while the cement and water mixtured serves as a binder between materials. To find out and study the behavior of each of these concrete constituents, it is necessary to know the characteristics of the materials made as constituents of the concrete. This study was conducted with the aim of comparing the most optimum type of coarse aggregate used and the comparison of the use of cement for coarse aggregate of crushed stone and coarse aggregate of gully originating from North Sumatera area, namely from the Wampu River in Binjai City as a concrete mixture to see its effect on compressive strength of concrete at the same concrete characteristics namely f’c 25 MPa. The results of the normal concrete mix design are obtained by using coarse aggregate of crushed stone and coarse aggregate of boulder in different amounts of cement. The coarse aggregate of crushed stone requires more cement with the amount of cement 411.1 kg/m3 than the coarse aggregate of gum with the amount of cement 388.9 kg/cm3.